Puisi Sebagai Media Resistensi Buruh Perempuan terhadap Penindasan di Lantai Produksi Pabrik Garmen: (Studi pada Puisi Karya DL, Buruh Perempuan Pabrik Garmen di KBN Cakung, Jakarta Utara) - Fauziah, Nurul; Suciati, Titis Nurwulan; Utami, Yessi Sri (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
Women workers in the garment industry face various forms of oppression, including violations of their reproductive rights, verbal abuse, and the silencing of their voices, while access to formal advocacy channels remains limited. Poetry has emerged as an alternative medium through which women workers can directly articulate their experiences of injustice. This study aims to describe and explain how a poem written by DL, a female garment factory worker at the Kawasan Berikat Nusantara (KBN) industrial estate in Cakung, North Jakarta, functions as a medium of symbolic resistance. The study employs a descriptive qualitative approach using Norman Fairclough’s Critical Discourse Analysis (CDA) framework, focusing on textual analysis through three language functions: ideational, relational, and identity. The research data consist of a 31-line poem written and publicly performed by its author during the commemoration of Marsinah Day and International Workers’ Day in 2025. The findings reveal that, at the ideational level, the poem represents oppression through a shift in agency from the abstract labor system to the supervisor as the immediate perpetrator, and finally to the factory as the institution that reproduces unequal power relations. At the relational level, the poem constructs a discursive position that develops from asserting reproductive rights to encouraging collective solidarity. At the identity level, the transformation from the first-person singular I to the first-person plural we signifies a shift from personal experience to shared political consciousness. These findings demonstrate that poetry functions as a medium for advocacy communication, an alternative public sphere (subaltern counterpublic), and a form of symbolic resistance that enables women workers to produce counter-knowledge about the injustices they experience.